2008
DOI: 10.3104/reports.2009
|View full text |Cite
|
Sign up to set email alerts
|

Medical conditions and medication use in adults with Down syndrome: A descriptive analysis

Abstract: Background: We examined the presence of medical conditions and medication use within a sample of adults with Down syndrome. Methods: Retrospective chart review using a sample of 141 adults with Down syndrome and age range of 30 to 65 years. Results: We identify 23 categories of commonly occurring medical conditions and 24 categories of medications used by adults with Down syndrome. Conclusion: Approximately 75% of older adults with Down syndrome in our sample experience memory loss and dementia. Hypothyroidism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
76
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 20 publications
8
76
2
2
Order By: Relevance
“…24 Osteoporosis was found more frequently in a younger sample (< 50 years old). 17 Comparing to these studies, we found lower rates of osteoporosis (1.7%), obesity (2.3%) and skin conditions (1.1%). DS adults seem to be at lower risk for malignant solid tumours 29 than the general population.…”
contrasting
confidence: 56%
See 4 more Smart Citations
“…24 Osteoporosis was found more frequently in a younger sample (< 50 years old). 17 Comparing to these studies, we found lower rates of osteoporosis (1.7%), obesity (2.3%) and skin conditions (1.1%). DS adults seem to be at lower risk for malignant solid tumours 29 than the general population.…”
contrasting
confidence: 56%
“…15,16 Nevertheless, suffering from DS results in an increased risk of developing psychological and neuropsychological conditions such as depression, anxiety and dementia. 4,6,10,16,17 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations